"It's all about trust!" a multilevel model of the effect of servant leadership on firefighters' group task performance, adaptivity and emotional exhaustion. - Perrier, Anthony; El Akremi, Assâad; Manville, Caroline; Molines, Mathieu (Public Administration Review)
How and why does servant leaders' behavior influence both performance (individual and collective) and emotional exhaustion within dynamic and extreme environments such as those of firefighters? We develop and test a multilevel model that integrates the principles of servant leadership with social exchange theory to explore how servant leadership positively influences collective task performance and how it strengthens adaptivity at the individual level and reduces emotional exhaustion. Our four‐wave and three‐source study sample comprised 303 firefighters nested in 45 fire stations. The results of multilevel structural equation model (MSEM) analyses indicate that at the individual level, servant leadership significantly predicts high adaptivity and low emotional exhaustion through the mediating influence of firefighters' felt trust and the trust climate. The implications of our results for theory and practice are discussed.